2013
DOI: 10.1021/cb400505a
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Down Lignin to High-Value Chemicals: The Conversion of Lignocellulose to Vanillin in a Gene Deletion Mutant of Rhodococcus jostii RHA1

Abstract: The aromatic polymer lignin represents a possible renewable source of aromatic chemicals, if biocatalytic routes for lignin breakdown can be developed. The availability of a genome sequence for Rhodococcus jostii RHA1, a bacterium that breaks down lignin, has allowed the application of a targeted pathway engineering strategy to lignin breakdown to produce vanillin, a valuable food/flavor chemical. A gene deletion strain of R. jostii RHA1 in which the vanillin dehydrogenase gene had been deleted, when grown on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
185
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 230 publications
(188 citation statements)
references
References 23 publications
2
185
0
1
Order By: Relevance
“…We have shown that a vanillin dehydrogenase gene deletion mutant of R. jostii RHA1 is able to accumulate vanillin, a high value aromatic product, when grown in minimal media containing wheat straw lignocellulose as carbon source [14]. We have also identified a B-type DyP in…”
Section: Introductionmentioning
confidence: 92%
“…We have shown that a vanillin dehydrogenase gene deletion mutant of R. jostii RHA1 is able to accumulate vanillin, a high value aromatic product, when grown in minimal media containing wheat straw lignocellulose as carbon source [14]. We have also identified a B-type DyP in…”
Section: Introductionmentioning
confidence: 92%
“…Another DyP from R. jostii, which was expressed in its native host, was shown to be active against wheat straw lignocellulose and produced potentially valuable products, namely vanillin and smaller amounts of ferulic acid and 4-hydroxybenzaldehyde. 61 …”
Section: Recombinant Lignin-degrading Peroxidasesmentioning
confidence: 99%
“…In contrast to fungal peroxidases, several bacterial DyPtype peroxidases and laccases have been expressed at high levels in Escherichia coli [81,82] and efficient lignin degradation has been demonstrated for DyP-type peroxidases [83]. For example, a bacterial DyP-type peroxidase expressed in a gene deletion strain of Rhodococcus jostii (its native producer) efficiently degraded wheat straw lignocellulose and produced vanillin and small amounts of ferulic acid and 4-hydroxybenzaldehyde [83]. Such processes have proven feasible in the laboratory, and the next challenge is to scale up production to industrial levels.…”
Section: Bacterial Lignin Degradationmentioning
confidence: 99%